The Seroprevalence of Hepatitis B Virus Among Children Attending Urban and Rural Hospitals - Alam, Mohd Shamsul; Khatoon, Soofia; Rima, Rezoana; Afrin, Sabina (Bangladesh Journal of Child Health, 2010)
Objectives: This study was conducted to a) find out and compare the period prevalence of HBsAg in children attending outdoor and indoor of an urban and a rural hospital b) determine the risk factors for Hepatitis B surface antigen positivity. Materials and Methods: Three hundred and twenty three children were included in this study. Among them 162 attended an urban hospital and 161 attended a rural hospital. Collected sera were examined for HBsAg by ELISA method in a standard laboratory. Results: Among the 162 urban children 17 (10.5%) were found to be HBsAg positive and among the 161 rural children 6 (3.7%) were found to be HBsAg positive. This difference is statistically significant (P value < 0.05). In urban area, 12 (16.2%) school aged, 3 (6%) pre-school children and 2 (5.5%) infants were found to be HBsAg positive. In rural area, more pre-school (6%) than school children (2.8%) were found to be HBsAg positive. In urban area, 11.5% male children and 9.5% female children were found to be HBsAg positive and in rural area, 5.2% male and 2.8% female children were to be HBsAg positive. Among 17 HBsAg positive cases who attended urban hospital, 11 (19.6%) had past history of jaundice and 6 (5.6%) had no past history of Jaundice (P value < 0.05). Among those 17 HBsAg positive cases, 13 (14.6%) had past history of inoculation within last 6 months and 4 (5.5%) had no such history. This difference is also statistically significant (P value < 0.005). Conclusion: Prevalence of positive HBsAg marker is fairly high in urban children (10.5%). Prevalence of HBsAg has no age and sex prediction. More sero-positive children in urban area have previous history of jaundice and history of inoculation in last 6 months, but no one in rural area had history of jaundice or inoculation within last 6 months. Key word: Serosurvilance; Hepatitis B virus. N.B. This publication is based on a dissertation DOI: 10.3329/bjch.v30i1.6178 Bangladesh J Child Health 2006; VOL 30 (1/2/3): 17-21